Screening and characterization of thermostable α-amylase-producing microbes from Karedhe North Buton Hot Springs, Indonesia - SARLAN SARLAN; RUGAIYAH A. ARFAH; ABDUL KARIM; ANITA ANITA; AHYAR AHMAD; PAULINA TABA; HARNINGSIH KARIM; SITI HALIMAH LAREKENG; DOROTHEA AGNES RAMPISELA; RUSDINA BTE LADJU (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Sarlan, Arfah RA, Karim A, Anita, Ahmad A, Taba P, Karim H, Larekeng SH, Rampisela DA, Ladju RB. 2025. Screening and characterization of thermostable α-amylase-producing microbes from Karedhe North Buton Hot Springs, Indonesia. Biodiversitas 26: 6513-6522. This study aimed to screen and characterize thermophilic α-amylase-producing bacteria from samples collected at Karedhe hot springs. A total of 23 bacterial isolates were obtained, where 8 isolates showed amylolytic activity. Amylase activity was assessed by iodine staining, which showed significant starch hydrolysis, indicated by clear zones around bacterial colonies. The results showed that isolate SRL40-1-3 had the largest clear zone (4 cm), while SRL40-2-1 produced a clear zone of 5.1 cm, indicating their potential for efficient starch degradation. Additionally, biochemical tests revealed distinct metabolic profiles, with only SRL40-1-3 able to use citrate as a carbon source. Specifically, isolates SRL40-1-3 and SRL40-2-1 were identified as Enterobacter sp. and Enterobacter hormaechei, respectively, based on molecular analysis. Further optimization studies showed that the optimal starch and CaCl2 concentrations for enzyme production were 1.25% and 0.12%, respectively, for SRL40-1-3. The optimum fermentation times were 42 h for SRL40-1-3 and 45 h for SRL40-2-1. In line with the results, the characterization of crude enzyme α-amylase showed that the optimum pH for both isolates was pH 6 at 50°C. Aside from pH, the optimum starch concentrations for crude enzyme in SRL40-1-3 and SRL40-2-1 were 0.015% and 0.01%, respectively. These results indicate that thermophilic bacteria from Karedhe hot springs have potential applications in industries requiring efficient starch degradation, such as bioethanol production and food processing.